Fractional Operators in p-adic Variable Exponent Lebesgue Spaces and Application to p-adic Derivative. (18th September 2021) - Chacón-Cortés, Leonardo Fabio; Rafeiro, Humberto
Abstract : In this paper, we prove the boundedness of the fractional maximal and the fractional integral operator in the p -adic variable exponent Lebesgue spaces. As an application, we show the existence and uniqueness of the solution for a nonhomogeneous Cauchy problem in the p -adic variable exponent Lebesgue spaces.